Analysis of Melamine on Powdered Milk-Based Diazoation Reactions with Eugenol Reagent By Spectrophotometry - Juliati Br Tarigan (Talenta Publisher, 2020)
The analysis of melamine on the milk-based diazotization reaction with eugenol was carried out. The presence of primary aromatic amine on melamine was reacted to sodium nitrite, while chloride acid formed diazonium salt, and then diazonium salt reacts with eugenol to form a colored azo compound. The absorbance was measured spectrophotometrically at a maximum wavelength of 470 nm. Analysis of melamine on the sample milk was determined by using a standard addition method. In this research, the optimization of concentration and incubation time was observed at the maximum formation of azo dyes. The optimization results were obtained at a concentration of eugenol of 9.10-3M, NaNO2 of 9.10-4 M, HCl of 0.25 M, and an incubation time of 5 minutes. The content of melamine in the milk sample was 2.513.10-5 M.